Implementasi E-Learning Pada Mata Pelajaran PAI Dimasa Pandemi Covid-19 - Riska Syahfitri; Desi Purnama Sari; Asri Wahyuni; Siti Fatimah; Hasrian Rudi Setiawan (Yayasan Rahmat Islamiyah, 2020)
This study aims to identify and obtain information on the implementation of E-learning ang the constrains of online teaching and learning process at home due to the existence of a pandemic covid-19. This study uses an exploratory case study method and its research approach uses a qualitative case study method that is used tonobtain information related to the constraints and consequances resulting from the pandemic covid19 on theaching and learning activities in several schools in Medan City. In this study, respondens who ware asked to conduct interview ware as many as 5 teacher in several schools in Medan City. For confidentiality purposes, respondents are given the initials R1,R2,R3,R4 and R5. This research uses interview method through social media by asking a number of questions which are arranged to be developed based on related literature. The results of this study are hare, are some obstacles experienced by students, teachers and parents in online teaching and learning activities, namely the mastery of technology is still lacking, additiona internet quota costs increase, there is assisting children learning, communication and socialization between students, teachers and parents are reduced and working hours become unlimited for teachers because they have to communicate and coordinate with parents, other techers and school principals. And from the negative side also causes children to be too spoiled with gadgets so that social values and behavior are less affective because the religious theaching process that has been given is not optimally carried out. Keywords: Implementation, E-learning PAI, Pandemic COVID-19.